Integración del enfoque psicoterapéutico sistémico y la psicología organizacional - Santillán, Washington (2017)
Integrate the two branches of Psychology (organizational and clinical), propose other practices to improve the WORK CLIMATE of the Organizations; Which includes Organizational Psychology and its processes and the wealth of Clinical Psychology using the Systemic Family Therapy model for the families of the workers of a Company, an example and proposal of this study. Allow me to suggest other management alternatives that lead us to a process of continuous improvement of the work environment of the Organizations, using innovative information, tools and strategies. I will try to show that these fields of psychology can be used harmonically, on the one hand, so that professionals in clinical psychology have a powerful tool in family therapy and that servesto improve the working environment of organizations, and on the other hand , The organizational psychologists, find new strategies and other innovative practices, in the improvement of this work climate, that is not necessarily the training, education andtraining of the personnel, if not, resort to other processes as; The emotional salary, familiarly responsible policies, CSR Corporate Social Responsibility or similar, to "achieve" important changes in the families and collaborators that form, and in turn, are a fundamental part of the companies in this XXI century.